REPRESENTASI HADIS HADIS HADIS DEMONSTRASI DI AKUN TIKTOK - Salsa Bintang Choiria (Tahdis: Jurnal Kajian Ilmu Al-Hadis, 2025)
This study examines the representation of hadiths about demonstrations on social media, particularly TikTok, which has become a new platform for the dissemination of religious discourse. Hadiths about demonstrations are generally understood as admonitions emphasizing obedience to those in authority and prohibiting rebellion, and are therefore often used to oppose demonstrations. However, on TikTok, these hadiths are presented in short videos with persuasive text, narrative, and visuals without contextual explanation, potentially leading to a narrowing of their meaning. The purpose of this study is to describe the form of hadith messages about demonstrations displayed in TikTok content and to analyze netizens' responses to them. The method used is qualitative content analysis, utilizing primary data in the form of TikTok videos about hadiths about demonstrations and secondary data from hadith literature and previous research. The results show that the representation of hadiths on social media is not only normative but can also be used as political legitimacy that influences public understanding.